Power equalizer for a series fuel cell architecture based on load tracking control. (September 2022) - Bizon, Nicu; Pierfederici, Serge; Bahrami, Milad; Thounthong, Phatiphat
Abstract: This paper analyses the safe operation of a multi-stack Polymer Electrolyte Membrane Fuel Cell (PEMFC) under normal conditions and partial faults using an innovative power-sharing technique based on Load-Following (LF) control. LF control references are designed based on the power flow balance to track the dynamic load profile. These references control the power flow of DC-DC boost converters connected to PEMFC stacks, performing power sharing and output voltage restoration as a final result. The behavior of multi-stack FC architecture is presented in conditions of partial drying and flooding of PEMFCs. If the transitory faults are short, the controllability of the boost converters is ensured by LF control and multi-stack FC architecture continues to safety operate in degraded-operation mode. Highlights: Operation in flood or drying conditions of the Fuel Cell (FC) membrane is considered. The power-sharing technique ensures FC system controllability under variable load. A safer control strategy for multi-stack FC system using the load-following (LF) control. LF control is effective for identical or different FC stacks as output power and voltage.